Factors Affecting Thai Fathers' Self-Efficacy to Support Exclusive Breastfeeding - Preeyakamon Krikitrat; Nantaporn Sansiriphun; Jirawan Deeluea; Sirirat Sonted; Wongduean Chaiwipassatorn; Daniel Bressington (MDPI AG, 2023)
Background: Breastfeeding is the ideal approach for feeding infants and is an important public health consideration. Successful exclusive breastfeeding initiation and duration is influenced by fathers' support. Paternal self-efficacy to support breastfeeding has also been shown to mediate infant feeding practices. The aim of this study was to investigate factors associated with Thai fathers' self-efficacy to support maternal exclusive breastfeeding. Methods: We adopted a cross-sectional survey design for this study. In total, 215 Thai fathers who had a partner with a term (37-42 weeks) pregnancy participated in the study. Data were collected from antenatal care clinics at two hospitals in Northern Thailand between June and August 2022. Participants completed a sociodemographic questionnaire, the Fathers' Attitude toward Exclusive Breastfeeding questionnaire, the Fathers' Knowledge about Exclusive Breastfeeding questionnaire, and the Breastfeeding Self-Efficacy Scale (Short-Form). Multiple linear regression and hierarchical regression were used to analyze factors influencing Thai fathers' self-efficacy to support maternal exclusive breastfeeding. Results: The mean breastfeeding self-efficacy score was 52.94 (SD = 8.58), indicating that fathers were confident they were able to support their partners' breastfeeding. Regression analysis revealed family type, fathers' attitude toward, and fathers' knowledge about exclusive breastfeeding significantly explaining 14.90% of the variance in paternal breastfeeding support self-efficacy. However, fathers' age, education, employment, income, and number of living children were not associated with their self-efficacy. Conclusions: The results demonstrated that family type and fathers' attitudes/knowledge about breastfeeding influenced their self-efficacy to support exclusive breastfeeding. Nurses should consider implementing breastfeeding interventions specific to fathers to enhance their attitudes and knowledge about breastfeeding, including increasing fathers' self-efficacy to support maternal exclusive breastfeeding efforts.